Secondary battery and apparatus equipped with said secondary battery

JP7657216B6Active Publication Date: 2026-10-13CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022532164
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-27
Publication Date
2026-10-13
Estimated Expiration
2040-03-27

Smart Images

  • Figure 0007657216000003
    Figure 0007657216000003
  • Figure 0007657216000004
    Figure 0007657216000004
  • Figure 0007657216000005
    Figure 0007657216000005
Patent Text Reader

Abstract

The present application discloses a secondary battery and a device including the secondary battery. The secondary battery includes a positive electrode sheet and a negative electrode sheet. The positive electrode sheet includes a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material. The negative electrode sheet includes a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material. The negative electrode active material includes a first material having artificial graphite and a second material having natural graphite. The positive electrode active material includes one or more types of layered lithium transition metal oxides and modified compounds thereof. The smoothness L of the surface of the negative electrode film sheet facing the negative electrode current collector satisfies 40≦L≦50. Alternatively, the positive electrode active material includes one or more types of lithium-containing phosphates with an olivine structure and modified compounds thereof. The smoothness L of the surface of the negative electrode film sheet facing the negative electrode current collector satisfies 45≦L≦55.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This application relates to the technical field of secondary batteries, and more particularly to secondary batteries and devices equipped with such secondary batteries. [Background technology]

[0002] Rechargeable batteries are widely used due to their advantages such as reliable operation, no pollution, and no memory effect. For example, as environmental protection issues become increasingly important, new energy vehicles are becoming more widespread, and the demand for power-type rechargeable batteries is exploding. However, as the range of applications for rechargeable batteries expands, high demands are placed on both their low-temperature power performance and energy density. Poor low-temperature power performance of rechargeable batteries affects their use in low-temperature environments. Energy density affects the battery's range, i.e., the time it can be used after a single charge. Therefore, improving the low-temperature power performance of rechargeable batteries while maintaining high energy density is an urgent technical challenge that needs to be addressed. [Overview of the project]

[0003] A first aspect of the present application provides a secondary battery comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material, wherein the positive electrode active material comprises one or more types from layered lithium transition metal oxides and modified compounds thereof, and the negative electrode active material comprises a first material having artificial graphite and a second material having natural graphite, and the surface of the negative electrode film sheet facing away from the negative electrode current collector brightness L satisfies 40 ≤ L ≤ 50, and preferably 43 ≤ L ≤ 48.

[0004] A second aspect of the present application provides a secondary battery comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material, wherein the positive electrode active material comprises one or more types from olivine-structured lithium-containing phosphates and modified compounds thereof, and the negative electrode active material comprises a first material having artificial graphite and a second material having natural graphite, and the surface of the negative electrode film sheet facing away from the negative electrode current collector brightness L satisfies 45 ≤ L ≤ 55, and preferably 48 ≤ L ≤ 52.

[0005] A third aspect of the present application provides a device comprising a secondary battery according to the first aspect of the present application.

[0006] Surprisingly, in the secondary battery of the present invention, the positive electrode sheet uses a specific positive electrode active material, the negative electrode sheet's negative electrode active material simultaneously contains artificial graphite and natural graphite, and the surface of the negative electrode film sheet facing away from the negative electrode current collector brightness By controlling the negative electrode sheet to a specific range, it is possible to have a high energy density while simultaneously effectively improving the active ion transport performance of the negative electrode sheet. Therefore, assuming the secondary battery has a high energy density, it is possible to achieve good low-temperature power performance. More preferably, the secondary battery can also have low high-temperature cycle expansion and a high high-temperature cycle capacity retention rate simultaneously. The apparatus of the present invention comprises the secondary battery according to the present invention and therefore has at least the same advantages as the aforementioned secondary battery. [Brief explanation of the drawing]

[0007] To more clearly explain the technical solutions of the embodiments of this application, the necessary drawings for the embodiments of this application are briefly introduced below. Naturally, the drawings described below represent only a portion of the embodiments of this application, and those skilled in the art can obtain further drawings based on these drawings without any creative work.

[0008] [Figure 1] This is a schematic diagram of one embodiment of a secondary battery. [Figure 2] This is an exploded view of Figure 1. [Figure 3] This is a schematic diagram of one embodiment of a battery module. [Figure 4] This is a schematic diagram of one embodiment of the battery pack. [Figure 5] This is an exploded view of Figure 4. [Figure 6] This is a schematic diagram of one embodiment of a device in which a secondary battery is used as a power source. [Modes for carrying out the invention]

[0009] The present application will be described in detail below, in conjunction with examples, to further clarify the purpose of the invention, the technical solution, and the beneficial technical effects. It should be understood that the examples described herein are for interpretation purposes only and not to limit the present application.

[0010] For simplicity, only a limited number of numerical ranges are explicitly disclosed in this specification. However, any lower limit may, in combination with any upper limit, form an unspecified range; any lower limit may, in combination with other lower limits, form an unspecified range; similarly, any upper limit may, in combination with any other upper limit, form an unspecified range. Also, although not explicitly stated, each point or single number between the endpoints of a range is included within that range. Thus, each point or single number, as its own lower or upper limit, may, in combination with any other point or single number, or in combination with other lower or upper limits, form an unspecified range.

[0011] In this specification, unless otherwise specified, "above" and "below" include the numbers being referred to, and "multiple types" in "one or more types" means two or more types.

[0012] The summary of the invention in this application is not intended to describe each embodiment or implementation disclosed herein. The following description will more specifically illustrate exemplary embodiments. Throughout this application, guidance is provided by a set of embodiments that can be used in various combinations. In each embodiment, the enumerations are used only as representative groups and should not be construed as exhaustive. secondary battery

[0013] A first aspect of the present application provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. During the charging and discharging process of the battery, active ions reciprocate between the positive electrode sheet and the negative electrode sheet through insertion and desorption. The electrolyte acts as a conductor of ions between the positive electrode sheet and the negative electrode sheet. [Positive electrode sheet]

[0014] The positive electrode sheet comprises a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two opposing surfaces in its thickness direction, and the positive electrode film sheet is laminated on any one or both of the two surfaces of the positive electrode current collector.

[0015] The positive electrode current collector can perform both conductive and current-collecting functions by using a material with good conductivity and mechanical strength. In some embodiments, aluminum foil can be used as the positive electrode current collector.

[0016] The positive electrode film sheet contains a positive electrode active material. The positive electrode active material can be a positive electrode active material for secondary batteries that is well known in this art. In some examples, the positive electrode active material may include one or more types of layered lithium transition metal oxides, olivine-structured lithium-containing phosphates, and modified compounds of the above materials.

[0017] In the context of "modified compounds," "modification" may refer to doping modification and / or surface coating modification of the material.

[0018] In some embodiments, the positive electrode active material includes one or more of layered lithium transition metal oxides and modified compounds thereof. As specific examples, the positive electrode active material includes, but is not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof. Preferably, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof.

[0019] In some embodiments, the positive electrode active material is Li a Ni b Co c M d M' e O f A g and Li having a coating layer on at least a part of the surface a Ni b Co c M d M' e O f A g includes one or more of them. Wherein 0.8≦a≦1.2, 0.5≦b<1, 0<c<1, 0<d<1, 0≦e≦0.1, 1≦f≦2, 0≦g≦1, M is selected from one or more of Mn and Al, M' is selected from one or more of Zr, Al, Zn, Cu, Cr, Mg, Fe, V, Ti and B, preferably includes one or more of Zr, Al, Zn and B, and A is selected from one or more of N, F, S and Cl.

[0020] In some embodiments, M is selected from Mn, and M' is selected from one or more of Zr, Al, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, preferably from one or more of Zr, Al, Zn, and B. Alternatively, M is selected from Al, and M' is selected from one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, preferably from one or more of Zr, Zn, and B.

[0021] By including a high-nickel ternary cathode active material, the cathode active material has a higher capacity per gram, thus increasing the energy density of the battery.

[0022] In some examples, Li a Ni b Co c M d M' e O f A g The particles can have a coating layer on 80% to 100% of their surface. Furthermore, Li a Ni b Co c M d M' e O f A g The particles may have a coating layer covering 90% to 100% of their surface.

[0023] In some other embodiments, the cathode active material comprises one or more of the olivine-structured lithium-containing phosphates and their modified compounds. Examples of olivine-structured lithium-containing phosphates include, but are not limited to, one or more of the lithium iron phosphate, lithium iron phosphate-carbon composites, lithium manganese phosphate, lithium manganese phosphate-carbon composites, and their modified compounds.

[0024] The lithium iron phosphate and carbon composite material may be one or more of the following: a coated composite material or an intercalated composite material. The coated composite material has a carbon coating layer on at least a portion of the surface of the lithium iron phosphate particles. For example, the carbon coating layer covers 80% to 100% (e.g., 90% to 100%) of the surface of the lithium iron phosphate particles. The carbon coating layer may contain one or more of the following: graphite, hard carbon, soft carbon, carbon black, coke, etc. In the intercalated composite material, lithium iron phosphate is dispersed in a carbon carrier. The carbon carrier may contain one or more of the following: graphite, hard carbon, soft carbon, carbon black, coke, etc.

[0025] The composite material of lithium manganese phosphate and carbon may be one or more of the following: a coated composite material or an intercalated composite material. The coated composite material has a carbon coating layer on at least a portion of the surface of the lithium manganese phosphate particles. For example, the carbon coating layer covers 80% to 100% (e.g., 90% to 100%) of the surface of the lithium manganese phosphate particles. The carbon coating layer may contain one or more of the following: graphite, hard carbon, soft carbon, carbon black, coke, etc. The intercalated composite material has lithium manganese phosphate dispersed in a carbon carrier. The carbon carrier may contain one or more of the following: graphite, hard carbon, soft carbon, carbon black, coke, etc.

[0026] In some embodiments, the positive electrode film sheet further selectively includes an adhesive. The type of adhesive is not particularly limited and can be selected according to the actual needs of those skilled in the art. For example, the adhesive for the positive electrode film sheet may include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

[0027] In some embodiments, the positive electrode film sheet further selectively contains a conductive agent. The type of conductive agent is not particularly limited and can be selected according to actual needs by those skilled in the art. For example, the conductive agent for the positive electrode film sheet may include one or more of the following: graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. [Negative electrode sheet]

[0028] The negative electrode sheet comprises a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two opposing surfaces in its thickness direction, and the negative electrode film sheet is laminated on any one or both of the two surfaces of the negative electrode current collector.

[0029] The negative electrode current collector can perform both conductive and current-collecting functions by using a material with good conductivity and mechanical strength. In some embodiments, copper foil can be used as the negative electrode current collector.

[0030] The negative electrode film sheet has a negative electrode active material, and the negative electrode active material comprises a first material having artificial graphite and a second material having natural graphite. Surprisingly, at the same time, the surface of the negative electrode film sheet facing away from the negative electrode current collector brightness When L is controlled within a specific range, the negative electrode sheet has a high energy density, and at the same time, the active ion transport performance of the negative electrode sheet is effectively improved. Assuming that the secondary battery using this sheet has a high energy density, it has been found that the low-temperature power performance is enhanced. More preferably, the secondary battery can also have low high-temperature cycle expansion and a high high-temperature cycle capacity retention rate.

[0031] brightnessL represents the surface roughness of the negative electrode film sheet facing the negative electrode current collector. By adjusting one or more of the following: the selection type of the first material, the selection type of the second material, the ratio of the first and second materials, the occupancy rate of natural graphite, the compressed density of the negative electrode film sheet, the type of conductive agent, the content of the conductive agent, etc., brightness L can be set within a desired range. The selection types of the first and second materials each include, but are not limited to, one or more of the following: composition, degree of graphitization, particle size distribution, surface coating modification, etc.

[0032] Through further research, the inventors have discovered that secondary batteries can exhibit superior performance by coordinating the design of the negative electrode sheet with the positive electrode active material used in the battery. Through diligent research, the inventors have found that when the positive electrode active material of the positive electrode sheet contains one or more types of layered lithium transition metal oxides and their modified compounds, the surface facing the negative electrode current collector in the negative electrode film sheet brightness We found that L satisfies the conditions 40 ≤ L ≤ 50.

[0033] The positive electrode active material contains one or more types of layered lithium transition metal oxides and their modified compounds, the negative electrode sheet's negative electrode active material contains both artificial graphite and natural graphite, and the negative electrode film sheet brightnessWhen L satisfies 40 ≤ L ≤ 50, an effective formulation is formed between the positive electrode active material and the negative electrode active material, fully utilizing the synergistic effect of their respective advantages and ensuring that the battery has a high energy density. Furthermore, by forming a surface porosity suitable for electrolyte infiltration in the negative electrode sheet, the solid-phase diffusion rate of active ions at the negative electrode is improved, thereby further enhancing the transport performance of active ions between the positive and negative electrodes. This significantly improves the dynamic performance of the battery, and even in low-temperature environments, the negative electrode rapidly receives active ions from the positive electrode, thus improving the low-temperature power performance of the secondary battery. This secondary battery is suitable for high-magnification charge and discharge, and the probability of lithium deposition occurring when high-magnification charging is performed at low temperatures is significantly reduced, while at the same time, the secondary battery can have high safety performance. In addition, by including one or more types of layered lithium transition metal oxides and their modified compounds in the positive electrode active material, a high surface density (e.g., 14 mg / cm³) can be achieved in the positive electrode sheet. 2 ~20 mg / cm³ 2 ) and compressed density (e.g. 3.3g / cm 3 ~3.5g / cm 3 In order to achieve this, the battery can have a high energy density.

[0034] In these examples, more preferably, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. This allows the above effects to be exhibited more effectively.

[0035] The inventors further stated that when the positive electrode active material contains one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds, the negative electrode active material simultaneously contains artificial graphite and natural graphite, and the negative electrode film sheet brightnessWe found that when L satisfies 40 ≤ L ≤ 50, the negative electrode sheet also possesses high cohesive and adhesive forces, further reducing the expansion of the negative electrode during the battery cycle process and improving the electrolyte retention capacity of the electrode sheet. As a result, it is possible to maintain a high volumetric energy density while simultaneously further enhancing dynamic performance.

[0036] Furthermore, because the negative electrode sheet has high ion and electron transport performance, the battery can have low resistance. In addition, the negative electrode sheet contains both artificial graphite and natural graphite, and the negative electrode film sheet brightness L satisfies 40 ≤ L ≤ 50, for example, L is 40.5, 41.6, 42.3, 43.5, 44.8, 45.5, 46.0, 46.5, 47.0, 47.5, 48.0, 48.5, or 49.7. This reduces the loss of active material due to poor particle contact and / or reduces battery polarization phenomena due to non-uniform electrolyte distribution, etc. Therefore, it is possible to achieve a high high-temperature cycle capacity retention rate in the battery.

[0037] In these embodiments, preferably, 43 ≤ L ≤ 48. brightness When L is within an appropriate range, the low-temperature power performance of the battery can be further improved, the high-temperature cycle expansion of the battery can be further reduced, and the high-temperature cycle capacity retention rate of the battery can be further increased.

[0038] The inventors, through further research, have found that the positive electrode active material contains one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds, and the negative electrode active material contains both artificial graphite and natural graphite, and the negative electrode film sheet brightness We found that if L satisfies 40 ≤ L ≤ 50, the performance of the battery can be further improved if the negative electrode active material further satisfies one or more of the following conditions.

[0039] In some preferred embodiments, the mass occupancy of natural graphite in the negative electrode active material may be 10% to 50%, preferably 15% to 30%, more preferably 15% to 25%, for example, 15%, 17%, 19%, 20%, 21%, and 23%. When an appropriate amount of natural graphite is included in the negative electrode active material, the negative electrode active material can be given a high capacity per gram, and in particular, the ion solid-phase diffusion rate of the negative electrode sheet can be further increased, thereby giving the battery a high energy density and further improving the power performance of the battery. In addition, an appropriate amount of natural graphite improves the adhesion between negative electrode active material particles and between the negative electrode active material and the negative electrode current collector, giving the negative electrode sheet high cohesive force and adhesion force, while simultaneously reducing side reactions on the negative electrode surface, thus allowing the battery to have low high-temperature cycle expansion. The high-temperature cycle performance of the battery can also be further improved.

[0040] In some preferred embodiments, the powder compression density of the negative electrode active material under a pressure of 30,000 N is 1.7 g / cm³. 3 ~1.9g / cm 3 It may be, preferably 1.75 g / cm³ 3 ~1.85g / cm 3 Therefore, if the powder compression density of the negative electrode active material is within an appropriate range, the negative electrode film sheet can be made to have a high compression density, thereby increasing the energy density of the battery.

[0041] In order to bring the powder compression density of the negative electrode active material within the above-mentioned predetermined range, in some preferred embodiments, the powder compression density of natural graphite under a pressure of 30,000 N is preferably 1.75 g / cm³. 3 ~1.9g / cm 3 More preferably, 1.75 g / cm³ 3 ~1.85g / cm 3 The powder compression density of artificial graphite under a pressure of 30,000 N is preferably 1.7 g / cm³. 3 ~1.9g / cm 3 More preferably, 1.8 g / cm³ 3 ~1.9g / cm 3 That is the case.

[0042] In some preferred embodiments, the degree of graphitization of the negative electrode active material may be 92% to 96%, preferably 93% to 95%. When the degree of graphitization of the negative electrode active material is within an appropriate range, it has a low powder resistivity, which reduces the resistance of the negative electrode sheet, and at the same time, it can have a layer spacing suitable for ion insertion and deinsertion, thereby further improving the low-temperature power performance of the battery. Furthermore, a negative electrode sheet using this negative electrode active material has high cohesive force and adhesive force, which can improve the low-cycle expansion performance of the battery.

[0043] The inventors further stated that the positive electrode active material comprises one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds, the negative electrode active material comprises artificial graphite and natural graphite, and the negative electrode film sheet brightness We found that when L is within a specific range, adjusting the degree of graphitization of the negative electrode active material to within that range can also improve the high-temperature cycle performance of the battery.

[0044] In order to bring the degree of graphitization of the negative electrode active material within the above-mentioned predetermined range, in some preferred embodiments, the degree of graphitization of natural graphite may be 95% to 98.5%, preferably 96% to 98%, more preferably 96.5% to 97.6%, and the degree of graphitization of artificial graphite may be 90% to 97.5%, preferably 90% to 95%, more preferably 91% to 93.5%.

[0045] In some preferred embodiments, the volume-average particle size D of the negative electrode active material v 50 may be 10 μm to 18 μm, preferably 11 μm to 15 μm, and more preferably 12 μm to 14 μm. D of the negative electrode active material v The smaller the value of 50, the more surface particles there are on the negative electrode film sheet, the greater the rebound of the electrode sheet after cold pressing, the more the surface particles are inserted into each other, and the roughness of the surface increases, thus affecting the surface of the negative electrode film sheet. brightnessThe small size of the negative electrode film sheet allows for increased electrolyte penetration and ion migration speed. When the Dv50 of the negative electrode active material is appropriate, it is possible to give the negative electrode film sheet a high active ion migration speed while simultaneously improving the capacity per gram of the negative electrode active material and reducing the surface active sites of the electrode sheet, thereby improving the low-temperature power performance, energy density, and high-temperature cycle performance of the battery.

[0046] D of the negative electrode active material v In order to bring 50 within the above-mentioned predetermined range, in some preferred embodiments, the D of natural graphite is used. v 50 may be 10 μm to 16 μm, preferably 10 μm to 14 μm, and more preferably 11 μm to 13 μm, and the D of artificial graphite v 50 may be 12 μm to 19 μm, preferably 12 μm to 16 μm, and more preferably 13 μm to 15 μm.

[0047] In some preferred embodiments, the compressed density of the negative electrode film sheet is 1.6 g / cm³. 3 ~1.8g / cm 3 Preferably, 1.65 g / cm³ 3 ~1.75g / cm 3 The most preferred concentration is 1.68 g / cm³. 3 ~1.73g / cm 3The positive electrode active material contains one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds, the negative electrode active material contains artificial graphite and natural graphite, the smoothness L of the negative electrode film sheet is within a specific range, and the compressed density of the negative electrode film sheet is within a predetermined range, thereby ensuring that the battery has a high energy density and simultaneously providing the negative electrode film sheet with high electrolyte permeability and good ion solid-phase diffusion rate, thus further improving the power performance of the battery. Furthermore, an appropriate compressed density can also protect the integrity of the negative electrode active material particle structure, improve the cohesive and adhesive strength of the negative electrode sheet, and is advantageous in reducing expansion and side reactions during the high-temperature cycle process of the battery, thus further improving the high-temperature cycle life of the battery.

[0048] In some preferred embodiments, the surface density of the negative electrode film sheet is 10 mg / cm². 2 ~13 mg / cm³ 2 Preferably, 10.5 mg / cm³ 2 ~11.5 mg / cm³ 2 The positive electrode material contains one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds, the negative electrode active material contains artificial graphite and natural graphite, and the negative electrode film sheet is brightness When L is within a specific range and the surface density of the negative electrode film sheet is within a predetermined range, the battery can have a high energy density. At the same time, the battery will have better ion and electron transport performance, further improving the battery's dynamic performance. In addition, if the battery satisfies the above design, polarization and side reactions will be reduced, further improving the battery's high-temperature cycle performance.

[0049] The inventors further stated that when the positive electrode active material of the positive electrode sheet contains one or more types of lithium-containing phosphates with an olivine structure and their modified compounds, preferably the surface facing away from the negative electrode current collector in the negative electrode film sheet brightness We found that L satisfies the condition 45 ≤ L ≤ 55.

[0050] The positive electrode active material contains one or more types of lithium-containing phosphates with an olivine structure and their modified compounds, the negative electrode sheet's negative electrode active material contains both artificial graphite and natural graphite, and the negative electrode film sheet brightness When L satisfies 45 ≤ L ≤ 55, an effective formulation is formed between the positive electrode active material and the negative electrode active material, fully utilizing the synergistic effect of their respective advantages. Assuming that the battery has a high energy density, the solid-phase diffusion rate of active ions between the positive and negative electrodes is improved, thereby further enhancing the battery's dynamic performance. Even in low-temperature environments, the negative electrode rapidly receives active ions from the positive electrode, thus improving the low-temperature power performance of the secondary battery. This secondary battery is suitable for high-magnification charge and discharge, and significantly reduces the probability of lithium deposition occurring when high-magnification charging is performed at low temperatures.

[0051] In these examples, the positive electrode active material more preferably includes one or more of the following: lithium iron phosphate, a composite material of lithium iron phosphate and carbon, and a modified compound thereof. This allows the above effects to be exhibited more effectively.

[0052] The inventors further stated that the positive electrode active material includes one or more types from lithium iron phosphate, a composite material of lithium iron phosphate and carbon, and modified compounds thereof, and the negative electrode active material includes artificial graphite and natural graphite simultaneously, and the negative electrode film sheet brightness We found that when L satisfies 45 ≤ L ≤ 55, expansion during the battery cycle process can be further reduced, and the electrolyte retention capacity between active materials in the electrode sheet is increased, which is advantageous for maintaining a high volumetric energy density while simultaneously improving dynamic performance.

[0053] Furthermore, because the negative electrode sheet has high ion and electron transport performance, the battery can have low resistance. In addition, the negative electrode sheet contains both artificial graphite and natural graphite, and the negative electrode film sheet brightnessThe condition L satisfies 45 ≤ L ≤ 55, thereby reducing the loss of active material due to poor particle contact and / or reducing battery polarization phenomena due to uneven electrolyte distribution. As a result, the battery can also maintain a high high-temperature cycle capacity.

[0054] In these embodiments, more preferably, 48 ≤ L ≤ 52. For example, L is 48.5, 49.0, 49.5, 50.0, 50.5, 51.0, or 51.5. brightness When L is within an appropriate range, the low-temperature power performance of the battery can be further improved, the high-temperature cycle expansion of the battery can be further reduced, and the high-temperature cycle capacity retention rate of the battery can be further increased.

[0055] The inventors, through further research, found that the positive electrode active material contains one or more types of lithium-containing phosphates with an olivine structure and their modified compounds, the negative electrode active material contains both artificial graphite and natural graphite, and the negative electrode film sheet brightness We found that if L satisfies 45 ≤ L ≤ 55, the performance of the battery can be further improved if the negative electrode active material further satisfies one or more of the following conditions.

[0056] In some preferred embodiments, the mass occupancy of natural graphite in the negative electrode active material may be 10% to 50%, preferably 15% to 50%, more preferably 35% to 50%, for example, 30%, 35%, 40%, 42%, 45%, 48%, or 50%. When the negative electrode active material contains an appropriate amount of natural graphite, the negative electrode active material can be given a high capacity per gram, and in particular, the ion solid-phase diffusion rate of the negative electrode sheet can be further increased, thereby giving the battery a high energy density and further improving the power performance of the battery. In addition, an appropriate amount of natural graphite improves the adhesion between negative electrode active material particles and between the negative electrode active material and the negative electrode current collector, giving the negative electrode sheet high cohesive force and adhesion force, while simultaneously reducing side reactions on the negative electrode surface, thus allowing the battery to have low high-temperature cycle expansion. The high-temperature cycle performance of the battery can also be further improved.

[0057] In some preferred embodiments, the powder compression density of the negative electrode active material at a pressure of 30,000 N is preferably 1.8 g / cm³. 3 ~1.9g / cm 3 More preferably, 1.82 g / cm³ 3 ~1.88 g / cm³ 3 Therefore, if the powder compression density of the negative electrode active material is within an appropriate range, the negative electrode film sheet can be made to have a high compression density, thereby increasing the energy density of the battery.

[0058] In order to bring the powder compressibility density of the negative electrode active material within the above-mentioned predetermined range, in some preferred embodiments, the powder compressibility density of natural graphite under a pressure of 30,000 N is preferably 1.85 g / cm³. 3 ~1.95g / cm 3 More preferably, 1.90 g / cm³ 3 ~1.95g / cm 3 Therefore, the powder compression density of artificial graphite under a pressure of 30,000 N is 1.75 g / cm³. 3 ~1.85g / cm 3 More preferably, 1.77 g / cm³ 3 ~1.80g / cm 3 That is the case.

[0059] In some preferred embodiments, the degree of graphitization of the negative electrode active material is 92% to 95%, preferably 93% to 94%. When the degree of graphitization of the negative electrode active material is within an appropriate range, it has a low powder resistivity, which reduces the resistance of the negative electrode sheet, and at the same time, it can have a layer spacing suitable for ion insertion and deinsertion, thereby further improving the low-temperature power performance of the battery. Furthermore, a negative electrode sheet using this negative electrode active material has high cohesive and adhesive strength, which can improve the low-cycle expansion performance of the battery.

[0060] The inventors further stated that the positive electrode active material comprises one or more types of lithium-containing phosphates with an olivine structure and modified compounds thereof, the negative electrode active material comprises artificial graphite and natural graphite, and the negative electrode film sheet brightness We found that when L is within a specific range and the degree of graphitization of the negative electrode active material is within the above range, the high-temperature cycle performance of the battery can also be improved.

[0061] In order to keep the degree of graphitization of the negative electrode active material within the above-mentioned predetermined range, in some preferred embodiments, the degree of graphitization of natural graphite may be 95% to 98.5%, preferably 97.5% to 98.5%, and the degree of graphitization of artificial graphite may be 89% to 95%, preferably 90% to 93%.

[0062] In some preferred embodiments, the volume-average particle size D of the negative electrode active material v 50 is 15 μm to 19 μm, preferably 16 μm to 18 μm. D of the negative electrode active material v The smaller the value of 50, the more surface pores there are on the negative electrode film sheet. brightness Because it is small, the penetration rate of the electrolyte and the migration rate of active ions in the negative electrode film sheet can be increased. v When 50 is appropriate, it is possible to give the negative electrode film sheet a high ion transfer rate, improve the capacity per gram of the negative electrode active material, and reduce the surface active area of ​​the electrode sheet, thereby improving the low-temperature power performance, energy density, and high-temperature cycle performance of the battery.

[0063] D of the negative electrode active material v In order to bring 50 within the above-mentioned predetermined range, in some preferred embodiments, the D of natural graphite is used. v 50 may be 15 μm to 20 μm, preferably 15 μm to 19 μm, and more preferably 16 μm to 18 μm, and the D of artificial graphite v 50 may be 14 μm to 19 μm, preferably 14 μm to 18 μm, and more preferably 15 μm to 17 μm.

[0064] In some preferred embodiments, the compressed density of the negative electrode film sheet is 1.5 g / cm³. 3 ~1.7g / cm 3Preferably, 1.55 g / cm³ 3 ~1.65g / cm 3 The positive electrode active material contains one or more types of lithium-containing phosphates with an olivine structure and their modified compounds, and the negative electrode active material contains artificial graphite and natural graphite simultaneously, and the negative electrode film sheet brightness When L is within a specific range and the compressed density of the negative electrode film sheet is within a predetermined range, it is possible to ensure that the battery has a high energy density, and at the same time, the negative electrode film sheet has high electrolyte permeability and a good ion solid-phase diffusion rate, thereby further improving the low-temperature power performance of the battery. In addition, an appropriate compressed density can also protect the integrity of the negative electrode active material particle structure, improve the cohesive force and adhesive force of the negative electrode sheet, and is advantageous in reducing expansion and side reactions during the high-temperature cycle process of the battery, thus further improving the high-temperature cycle life of the battery.

[0065] In some preferred embodiments, the surface density of the negative electrode film sheet is 7 mg / cm². 2 ~10 mg / cm³ 2 Preferably, 7 mg / cm³ 2 ~8 mg / cm³ 2 The positive electrode material contains one or more types of lithium-containing phosphates with an olivine structure and their modified compounds, the negative electrode active material contains artificial graphite and natural graphite, and the negative electrode film sheet is brightness When L is within a specific range and the surface density of the negative electrode film sheet is within a predetermined range, the battery can have a high energy density. At the same time, the battery will have better ion and electron transport performance, further improving the battery's dynamic performance. In addition, if the battery satisfies the above design, polarization and side reactions will be reduced, further improving the battery's high-temperature cycle performance.

[0066] In any negative electrode sheet of the present application, the negative electrode active material may optionally further include one or more types from hard carbon, soft carbon, silicon-based materials, and tin-based materials. The silicon-based material can be selected from one or more types from elemental silicon, silicon-oxygen compounds, silicon-carbon composites, and silicon alloys. The tin-based material can be selected from one or more types from elemental tin, tin-oxygen compounds, and tin alloys.

[0067] In some embodiments, the negative electrode film sheet may further contain an adhesive. For example, the adhesive for the negative electrode film sheet can be selected from one or more of the following: polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0068] In some embodiments, the negative electrode film sheet further selectively contains a thickening agent. For example, the thickening agent may be sodium carboxymethylcellulose (CMC-Na).

[0069] In some embodiments, the negative electrode film sheet further selectively contains a conductive agent. For example, the conductive agent for the negative electrode film sheet can be selected from one or more types of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0070] In this application, the negative electrode film sheet brightnessL is a well-known term in this field and can be measured by methods known in this field. An example measurement method is as follows: First, the negative electrode sheet is placed below the measuring port of a precision colorimeter (e.g., multi-function precision colorimeter NR60CP), the measuring port of the precision colorimeter is brought close to the negative electrode film sheet and its position is adjusted to achieve alignment, the measurement is performed and the measurement result is recorded. To ensure the accuracy of the measurement result, 10 groups of test samples are taken and the average value of these 10 groups of test samples is calculated.

[0071] In this application, the powder compressibility density of the negative electrode active material is a well-known concept in the art and can be measured by methods known in the art. For example, it can be measured using an electronic pressure tester (e.g., UTM7305), referring to GB / T 24533-2009. An exemplary measurement method is as follows: A test powder of mass M is placed in a compaction mold (bottom area S), a different pressure (30,000 N is used in this application) is set, the pressure is held for 30 seconds, the pressure is released, wait for 10 seconds, and the thickness H of the powder after compaction under that pressure is read by the instrument. The powder compressibility density of the negative electrode active material under that pressure is = M / (H × S).

[0072] In this application, the surface density of the negative electrode film sheet is a well-known concept in the art and can be measured by methods known in the art. For example, take a negative electrode sheet that has been coated on one side and cold-pressed (if it is a double-sided coated electrode sheet, first wipe off the negative electrode film sheet from one side), punch it out into a small circular sheet with an area S1, weigh it, and label it M1. Next, wipe off the negative electrode film sheet from the weighed negative electrode sheet, weigh the negative electrode current collector, label it M0, and the surface density of the negative electrode film sheet = (weight of negative electrode sheet M1 - weight of negative electrode current collector M0) / S1.

[0073] In the present application, the compressed density of the negative electrode film sheet has a well-known meaning in the art, and can be measured by a method known in the art. For example, take the negative electrode sheet after single-side coating and cold pressing (in the case of an electrode sheet coated on both sides, first, the negative electrode film sheet on one side thereof can be wiped off), measure the thickness of the negative electrode film sheet, then further measure the areal density of the negative electrode film sheet according to the above method, where the compressed density of the negative electrode film sheet = areal density of the negative electrode film sheet / thickness of the negative electrode film sheet.

[0074] In the present application, D of the negative electrode active material v 50 has a well-known meaning in the art, and can be measured by a method known in the art. For example, referring to the standard GB / T 19077.1-2016, the measurement can be carried out using a laser particle size analyzer (for example, Malvern Master Size 3000). Among them, D v The physical definition of 50 is the corresponding particle size when the cumulative volume distribution percentage of the material reaches 50%.

[0075] In the present application, the graphitization degree of the negative electrode active material has a well-known meaning in the art, and can be measured by a method known in the art. For example, the measurement can be carried out using an X-ray diffractometer (for example, Bruker D8 Discover). The measurement refers to JIS K 0131-1996 and JB / T 4220-2011, and d 002 After measuring the magnitude of, the graphitization degree can be calculated based on the formula G=(0.344-d 002 ) / (0.344-0.3354)×100%, where d 002 is the interlayer spacing in the graphite crystal structure calculated in nm. In the X-ray diffraction analysis test, CuK α radiation is used as the radiation source, the radiation wavelength λ=1.5418Å, the scanning 2θ angle range is 20° to 80°, and the scanning speed is 4° / min. [Electrolyte]

[0076] The electrolyte is located between the positive electrode sheet and the negative electrode sheet and plays a role in conducting ions. This invention does not particularly limit the type of electrolyte and can be selected according to the requirements. For example, the electrolyte can be selected from at least one of solid electrolytes and liquid electrolytes (i.e., electrolyte solution).

[0077] In some examples, an electrolyte solution is used as the electrolyte. The electrolyte solution contains an electrolyte salt and a solvent.

[0078] In some examples, the electrolyte salt can be selected from one or more of the following: LiPF6 (lithium hexafluoride phosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoride arsenate), LiFSI (lithium bisfluorosulfonylimide lithium), LiTFSI (lithium bis(trifluoromethanesulfone)imide), LiTFS (lithium trifluoromethanesulfonate lithium), LiDFOB (lithium difluoro(oxalate) borate), LiBOB (lithium bisoxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalate) phosphate), and LiTFOP (lithium tetrafluorooxalate phosphate).

[0079] In some examples, the solvent can be selected from one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0080] In some embodiments, the electrolyte further selectively includes additives. For example, the additives may include additives for negative electrode film formation, additives for positive electrode film formation, or additives that can improve specific performance of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high-temperature performance of the battery, or additives that improve the low-temperature performance of the battery. [Separator]

[0081] A separator is further included in secondary batteries using an electrolyte, and in some secondary batteries using a solid electrolyte. The separator is placed between the positive electrode sheet and the negative electrode sheet to perform a separating function. The present application does not particularly limit the type of separator, and any well-known porous separator having good chemical and mechanical stability can be selected. In some embodiments, the material of the separator can be selected from one or more types of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multilayer composite film. If the separator is a multilayer composite film, the materials of each layer may be the same or different.

[0082] This invention does not particularly limit the shape of the secondary battery, and it may be cylindrical, rectangular, or any other shape. Figure 1 shows a secondary battery 5 with a rectangular structure as an example.

[0083] In some embodiments, the secondary battery may include an outer casing. This casing is used to seal the positive electrode sheet, the negative electrode sheet, and the electrolyte.

[0084] In some embodiments, the casing of the secondary battery may be a soft pack, for example, a bag-shaped soft pack. The material of the soft pack may be plastic, for example, one or more types of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc. The casing of the secondary battery may also be a hard case, for example, a hard plastic case, an aluminum case, or a steel case.

[0085] In some embodiments, referring to Figure 2, the exterior comprises a case 51 and a cover plate 53. The case 51 comprises a bottom plate and side plates connected to the bottom plate, and the bottom plate and side plates surround a storage chamber. The case 51 has an opening that communicates with the storage chamber, and the cover plate 53 covers the opening so as to seal the storage chamber.

[0086] The positive electrode sheet, negative electrode sheet, and separator can be formed into an electrode assembly 52 through a winding or lamination process. The electrode assembly 52 is sealed within the housing chamber. An electrolyte solution can be used as the electrolyte, and the electrolyte solution is impregnated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and can be adjusted according to demand.

[0087] In some embodiments, the secondary batteries can be assembled to form a battery module, and the number of secondary batteries included in the battery module may be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0088] Figure 3 shows an example of a battery module 4. Referring to Figure 3, in the battery module 4, the multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, they can be arranged in any other manner. Furthermore, these multiple secondary batteries 5 may be fixed together with fasteners.

[0089] Selectively, the battery module 4 includes a case having additional housing space, and multiple secondary batteries 5 are housed in this housing space.

[0090] In some embodiments, the above battery modules can be further assembled to form a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0091] Figures 4 and 5 show an example of a battery pack 1. Referring to Figures 4 and 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 arranged inside the battery box. The battery box comprises an upper housing 2 and a lower housing 3, the upper housing 2 being positioned to cover the lower housing 3 and forming a sealed space for housing the battery modules 4. The plurality of battery modules 4 may be arranged inside the battery box in any manner. [Manufacturing method]

[0092] A method for manufacturing a secondary battery may include the step of assembling a negative electrode sheet, a positive electrode sheet, and an electrolyte to form a secondary battery. In some embodiments, the positive electrode sheet, a separator, and a negative electrode sheet are sequentially wound or stacked such that the separator acts as a separator between the positive and negative electrode sheets to obtain an electrode assembly (i.e., a core). The core is placed in an outer casing, the electrolyte is injected, and it is sealed to obtain a secondary battery.

[0093] In some embodiments, the manufacturing of a secondary battery may further include a step of manufacturing a positive electrode sheet. For example, a uniform positive electrode slurry can be formed by dispersing a positive electrode active material, a conductive agent, and an adhesive in a solvent (e.g., N-methylpyrrolidone, abbreviated as NMP). The positive electrode slurry is applied to a positive electrode current collector, and after processes such as drying and cold pressing, a positive electrode sheet is obtained.

[0094] In some embodiments, the manufacturing of a secondary battery may further include a step of manufacturing a negative electrode sheet. For example, a negative electrode active material, an adhesive, and a selectable thickener and conductive agent can be dispersed in a solvent to form a uniform negative electrode slurry, the solvent of which may be deionized water. The negative electrode slurry is applied to a negative electrode current collector, and after processes such as drying and cold pressing, a negative electrode sheet is obtained. Device

[0095] A second aspect of the present application provides a device comprising a secondary battery according to the first aspect of the present application. The secondary battery may be used as a power source for the device, or as an energy storage unit for the device. The device may be, but is not limited to, mobile devices (e.g., mobile phones, laptop computers, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0096] The device can be configured to use a secondary battery, a battery module, or a battery pack, depending on the user's needs.

[0097] Figure 6 shows an example of a device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. Battery packs or battery modules may be used to meet the device's requirements for high power and high energy density of secondary batteries.

[0098] Other examples of devices may include mobile phones, tablets, laptop computers, etc. Such devices generally require lightweight and thin designs and can use rechargeable batteries as a power source. Examples

[0099] The following examples illustrate the disclosures in this application in more detail. These examples are for illustrative purposes only, and modifications and changes within the scope of the disclosures will be obvious to those skilled in the art. Unless otherwise specified, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to common methods and can be used directly without further processing. The apparatus used in the examples is also commercially available. Example 1 Positive electrode sheet

[0100] Positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM811), conductive agent Super P, and adhesive PVDF are thoroughly stirred and mixed with an appropriate amount of NMP in a mass ratio of 96.5:1.5:2 to form a uniform positive electrode slurry. The positive electrode slurry is applied to two surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained. Negative electrode sheet

[0101] The negative electrode active material (75% by weight artificial graphite and 25% by weight natural graphite), conductive agent Super P, adhesive SBR, and thickener CMC-Na are thoroughly stirred and mixed with an appropriate amount of deionized water in a mass ratio of 96.2:0.8:1.8:1.2 to form a uniform negative electrode slurry. The negative electrode slurry is applied to two surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained. Separator

[0102] Use a PP / PE composite separator. Manufacturing of electrolyte

[0103] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1, then LiPF6 is uniformly dissolved in the above solution to obtain an electrolytic solution. In this electrolytic solution, the concentration of LiPF6 is 1 mol / L. Manufacturing of rechargeable batteries

[0104] A positive electrode sheet, a separator, and a negative electrode sheet are sequentially laminated and wound to obtain an electrode assembly. The electrode assembly is placed in an outer package, the above-prepared electrolytic solution is injected, and after undergoing steps such as sealing, standing, formation, and aging, a secondary battery is obtained. Examples 2 to 25 and Comparative Examples 1 to 12

[0105] The manufacturing method is similar to that of Example 1, with the difference being that by adjusting the relevant parameters in the negative electrode sheet manufacturing process, the corresponding secondary battery is obtained, and the details are as shown in Table 1 and Table 2. The batteries of Examples 1 to 12 and Comparative Examples 1 to 6 in Table 1 all use NCM811 as the positive electrode active material, and the positive electrode film sheet has a compaction density of 3.5 g / cm 3 and an areal density of 18.5 mg / cm 2 The batteries of Examples 13 to 25 and Comparative Examples 7 to 12 in Table 2 all use lithium iron phosphate (abbreviated as LFP) as the positive electrode active material, and the positive electrode film sheet has a compaction density of 2.3 g / cm 3 and an areal density of 16.2 mg / cm 2 . Test section

[0106] In the following tests, when the positive electrode active material is lithium nickel cobalt manganese oxide, the discharge cutoff voltage is 2.8 V, and the charge cutoff voltage is 4.2 V. When the positive electrode active material is lithium iron phosphate, the discharge cutoff voltage is 2.5 V, and the charge cutoff voltage is 3.65 V. 1) Cycle expansion rate test of negative electrode sheet

[0107] The initial thickness of the negative electrode sheet in each example and comparative example is denoted as H0. Next, a charge-discharge test is performed on the battery in a 25°C environment, and constant current discharge is performed with a discharge current of 1.0C (i.e., the current value that completely discharges the theoretical capacity in 1 hour) until the discharge cutoff voltage is reached. Then, constant current charging is performed with a charging current of 1.0C until the charge cutoff voltage is reached, followed by constant voltage charging until the current reaches 0.05C. At this point, the battery is fully charged, i.e., 100% SOC (State of Charge). After the fully charged battery is left to stand for 5 minutes, constant current discharge is performed with a discharge current of 1.0C until the discharge cutoff voltage is reached. The discharge capacity at this time is the actual capacity of the battery at 1.0C and is denoted as C0. At 45°C, the secondary battery is subjected to a 1C0 / 1C0 charge-discharge cycle at 100% DOD (100% depth of discharge, i.e., completely discharged after full charge) on a Neware charge-discharge test machine. The cycle is stopped when the number of cycles reaches 600. Subsequently, the secondary battery is charged to 100% SOC, disassembled, and the thickness of the corresponding negative electrode sheet is measured and recorded as H1. The cycle expansion rate of the negative electrode sheet after 600 1C0 / 1C0 cycles at 45°C for the battery is (H1 / H0-1) × 100%. 2) Low-temperature lithium deposition performance test of batteries

[0108] First, measure the actual capacity C0 of the battery at 1.0C according to method 1). Next, place the battery in a -10°C environment and charge it with a constant current of xC0 until it reaches the charge cutoff voltage. Then, charge it with a constant voltage until the current reaches 0.05C0, let it stand for 5 minutes, disassemble the core, and observe the lithium deposition status at the interface. If lithium is not deposited on the negative electrode surface, increase the charging rate and continue the test until lithium is deposited on the negative electrode surface. Record the maximum charging rate at which lithium is not deposited on the negative electrode surface and determine the low-temperature lithium deposition rate. 3) High-temperature cycle performance test of the battery

[0109] First, measure the actual capacity C0 of the battery at 1.0C according to method 1). Next, in a 60°C environment, charge the battery with a constant current of 1.0C0 until it reaches the charge cutoff voltage, then charge it with a constant voltage until the current drops to 0.05C0, and finally discharge it with a constant current of 1.0C0 until it reaches the discharge cutoff voltage. This constitutes one charge-discharge cycle, and the discharge capacity recorded is the discharge capacity of the first cycle. Subsequently, perform charge and discharge cycles continuously, record the discharge capacity value during the cycle process, and calculate the capacity retention rate for each cycle. If the cycle capacity retention rate drops to 80% of the initial cycle discharge capacity, record the number of cycles the battery has undergone.

[0110] [Table 1]

[0111] [Table 2]

[0112] As can be seen from the comparative results of Examples 1-12 and Comparative Examples 1-6, the positive electrode sheet contains one or more types of layered lithium transition metal oxides and their modified compounds, the negative electrode sheet contains artificial graphite and natural graphite simultaneously, and the surface of the negative electrode film sheet facing away from the negative electrode current collector brightness When L satisfies 40 ≤ L ≤ 50, and especially 43 ≤ L ≤ 48, the negative electrode sheet can exhibit low cycle expansion during the charge-discharge process, while simultaneously effectively improving the lithium-ion transport performance of the negative electrode sheet. Assuming the secondary battery has a high energy density, this enhances the low-cycle expansion performance and low-temperature power performance of the secondary battery. Furthermore, the capacity retention rate during the high-temperature cycle process of the battery can also be significantly improved.

[0113] As can be seen from the comparative results of Examples 13-25 and Comparative Examples 7-12, the positive electrode sheet contains one or more types of lithium-containing phosphates with an olivine structure and their modified compounds, the negative electrode sheet contains artificial graphite and natural graphite simultaneously, and the surface of the negative electrode film sheet facing away from the negative electrode current collector brightness When L satisfies 45 ≤ L ≤ 55, and especially 48 ≤ L ≤ 52, the negative electrode sheet can exhibit low cycle expansion during the charge-discharge process, while simultaneously effectively improving the lithium-ion transport performance of the negative electrode sheet. Assuming the secondary battery has a high energy density, this enhances the low-cycle expansion performance and low-temperature power performance of the secondary battery. More preferably, the capacity retention rate during the high-temperature cycle process of the battery can also be significantly improved.

[0114] Furthermore, as can be seen from the results of Examples 6-8 and 18-21, when the positive electrode sheet uses a specific positive electrode active material, the negative electrode sheet contains both artificial and natural graphite, and the mass occupancy rate of natural graphite in the negative electrode active material is within a specific range, it is even more advantageous for achieving high low-cycle expansion performance, low-temperature power performance, and high-temperature cycle performance simultaneously in the battery.

[0115] As can be seen from the results of Examples 9-12 and 22-25, when the positive electrode sheet uses a specific positive electrode active material, the negative electrode sheet contains both artificial and natural graphite, and the compressed density and / or surface density of the negative electrode film sheet are within a specific range, it is even more advantageous for the battery to simultaneously achieve high low-cycle expansion performance, low-temperature power performance, and high-temperature cycle performance.

[0116] The above description only concerns specific embodiments of the present application; however, the scope of protection of the present application is not limited to these, and a person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed herein, and such modifications or substitutions should be included within the scope of the present application. Therefore, the scope of protection of the present application shall be equivalent to the scope of protection of the claims.

Claims

1. A secondary battery comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material, The positive electrode active material comprises one or more types of layered lithium transition metal oxides and their modified compounds, wherein the modified compound is a layered lithium transition metal oxide that undergoes doping modification and / or surface coating modification. The negative electrode active material comprises a first material having artificial graphite and a second material having natural graphite. The brightness L of the surface of the negative electrode film sheet facing away from the negative electrode current collector satisfies 40 ≤ L ≤ 50. The aforementioned lightness L is measured by a colorimeter. Secondary battery.

2. The mass occupancy of natural graphite in the negative electrode active material is 10% to 50%. The secondary battery according to claim 1.

3. The powder compression density of the negative electrode active material under a pressure of 30,000 N is 1.7 g / cm³. 3 ~1.9 g / cm 3 That is, The secondary battery according to claim 1 or 2.

4. The degree of graphitization of the negative electrode active material is 92% to 96%, and the degree of graphitization is measured by the method described in the specification. A secondary battery according to any one of claims 1 to 3.

5. Volume average particle size D of the negative electrode active material v 50 is between 11 μm and 15 μm. A secondary battery according to any one of claims 1 to 4.

6. The compressed density of the negative electrode film sheet is 1.6 g / cm³. 3 ~1.8 g / cm 3 and / or, The surface density of the negative electrode film sheet is 10 mg / cm². 2 ~13 mg / cm³ 2 That is, A secondary battery according to any one of claims 1 to 5.

7. The positive electrode sheet comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material, A secondary battery comprising a negative electrode sheet, a negative electrode current collector, and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material, The positive electrode active material comprises one or more types of lithium-containing phosphates with an olivine structure and their modified compounds, wherein the modified compound is a compound that undergoes doping modification and / or surface coating modification. The negative electrode active material comprises a first material having artificial graphite and a second material having natural graphite. The brightness L of the surface of the negative electrode film sheet facing away from the negative electrode current collector satisfies 45 ≤ L ≤ 55. The aforementioned lightness L is measured by a colorimeter. Secondary battery.

8. The mass occupancy of natural graphite in the negative electrode active material is 10% to 50%. The secondary battery according to claim 7.

9. The powder compression density of the negative electrode active material under a pressure of 30000 N is 1.8 g / cm 3 to 1.9 g / cm 3 , The secondary battery according to claim 7 or 8.

10. The degree of graphitization of the negative electrode active material is 92% to 95%, and the degree of graphitization is measured by the method described in the specification. A secondary battery according to any one of claims 7 to 9.

11. Volume-average particle size D of the anode active material v 50 is between 15 μm and 19 μm. A secondary battery according to any one of claims 7 to 10.

12. The compressed density of the negative electrode film sheet is 1.5 g / cm³. 3 ~1.7 g / cm 3 And, and / or, The surface density of the negative electrode film sheet is 7 mg / cm². 2 ~10 mg / cm³ 2 That is, A secondary battery according to any one of claims 7 to 11.

13. An apparatus comprising a secondary battery according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • High-voltage and high-volumetric-energy-density long-life lithium ion battery and preparation method thereof

    CN106252569A

  • Low-temperature lithium-ion battery

    CN109888368A

  • Anode material for lithium secondary battery, manufacturing method of the same, lithium secondary battery anode using the same, and lithium secondary battery

    JP2005259689A

  • Negative electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and method for manufacturing negative electrode material for nonaqueous electrolyte secondary battery

    JP2016152077A